The effective role of hydroxyapatite- based composites in anticancer drug- delivery systems - Saber-Samandari, Samaneh; Nezafati, Nader; Saber-Samandari, Saeed (Begell House Inc. orders@begellhouse.com, 2016)
Tumors consist of a heterogeneous population of cancer cells carrying multiple genetic mutations. During the past few decades, efforts have focused on curing cancer using various methods. However, traditional cancer therapies still carry some drawbacks, such as limited application for only a few cancer types, killing of normal cells, poor specificity, and associated toxicity. To overcome these disadvantages, drug-delivery methods that emphasize biomaterials have been developed and applied to optimize cancer treatments. Hydroxyapatite (HAP) is a biocompatible inorganic material that can be applied in biomedical drug-delivery applications. This review discusses the features and properties of HAP that make it an effective biomaterial and provides a comprehensive summary of recent studies in which HAP and composites containing HAP were applied as anticancer drug carriers. We believe that HAP-based composites show great promise for cancer treatment using controlled release of therapeutic agents, leading to enhanced efficiency, selective release of drugs, and prohibition of cancer cell proliferation. © 2016 Begell House, Inc.
Keywords: Cancer; Chemotherapy; Composites; Drug delivery; Hydroxyapatite